Hubungan Konsumsi Soft Drink Dengan Usia Menarche Pada Remaja Putri Di Sd Pacar Timbulharjo - Desi Ekawati; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
In girls, early puberty is characterized by menarche. Factors that can affect the age of menarche include socio-economic, BMI, nutritional status, including soft drink consumption. Soft drink consumption in teenagers is very high with the content in soft drinks such as caffeine and artificial sweeteners. There is a shift in the age of menarche which tends to be earlier, especially in developing countries. Increased consumption of sweetened beverages, such as soft drinks, is considered the cause This research aims to find out. The relationship between soft drink consumption and menarche age in adolescent girls at Pacar Elementary School. This study used an observational analytical study with a cross sectional design. The research location is at Pacar Elementary School, the research was conducted in February 2024 with a total of 45 respondents. Sampling was done using purposive sampling techniques. The analysis in this study used a brivariate analysis with a statistical test with Chi-square to determine the relationship between soft drink consumption and menarche age in adolescent girls The results of the study showed that there was a relationship between soft drink consumption and menarche age as shown with a value of p=0.00 (<0.05). The value of p=0.00 shows that the results of the tested study have a statistically significant relationship (p<0.05). Conclusion There is a relationship between soft drink consumption and menarche age in adolescent girls.